Rede Bem Cuidar-RS: atenção à saúde da população idosa na percepção de gestores e profissionais - Savariz, Alan Rafael Martins (2024)
The demographic transition of an aging Brazilian population brings with itself new demands to the healthcare system, arising the necessity to adequate it to assist these new situations and to innovate on new health care methods for the elderly. The health of the elderly population has its own characteristics and requires specific attention. Considering this context, the Health Secretary of Rio Grande do Sul implemented "Rede Bem Cuidar – RS" (Well Care Network –RS), a program that aims for the improvement of healthcare practices and for a healthy aging of the population. This study has the objective of evaluate the implementation and development of Rede Bem Cuidar-RS, from the perspective of managers and professionals in Primary Health Care. Methodologically, it is a study with a qualitative approach, analytic, based on elderly population healthcare policies. It took place in the municipalities that cover the 20th health region of the state of Rio Grande do Sul, in which participated twelve managers and twelve professionals that act on Rede Bem Cuidar – RS. The professionals included medics, nurses, psychologists, nutritionists, and dentists. The data was collected between April and June of 2024 through individual and in-person interviews, with the aid of a script previously elaborated from information contained in the evaluation instrument of management in primary attention healthcare and adjusted to the study. The interview accounts were recorded and transcribed in their entirety. The data analysis employed the examination precepts of the thematic content. The study respected the ethical aspects of researching with human beings. The results made evident the understanding of managers and professionals on elderly population health care considering the implementation of Rede Bem Cuidar – RS. It was revealed a diversity of opinions and experiences, elucidating both the advances and the challenges that were faced in the execution of RBC – RS. The general perception was that development occurred coming from the goals determined by the program, in addition to positive reviews regarding the financial resources derived from the RBC – RS. It can be concluded that the program holds potential in changing and qualifying health care for elderly people. It is suggested research that takes into consideration other scenarios and participants, with the example of the users, widening the knowledge regarding the theme.